THE MULTIFUNCTIONAL FORMATION HEALTH FROM THE PERSPECTIVE OF THE RESIDENT - Natalia Gonçalves Mateus; Daniel Aragão Machado (Universidade Federal do Estado do Rio de Janeiro, 2018)
Objective: To describe the experiences as a member of the 1st class of Nurse Residency Multidisciplinary Health of Gaffrée Guinle Hospital and describe the activities performed during the practical and theoretical course. Methods: This was a descriptive study of situational analysis and characterized as an experience report. Results: The program, which began in February 2011, consisted of professional nursing, nutrition, speech pathology and physiotherapy. It has duration of two years and a workload of 60 hours a week. Displays fields of activity as different scenarios of the hospital and, with the intent to promote the experience of comprehensive health care, with a period for the Primary Care. Conclusion: The prolonged interaction between residents multidisciplinary provided a great learning experience in relation to the collective, increasing respect, appreciation and knowledge among professions.